Application of FF-QuantSC for the Precise Estimation of Fetal Fraction in Non-invasive Prenatal Testing in Two SRY-Translocation Cases - Zeng, Yan; Gao, Jiong; Yuan, Hua; Zhou, Lijun; Cheng, Dehua; Che, Ming; Qian, Yandi; Fan, Jiaming; Zhang, Lifang; Qian, Feiyan; Gao, Yuling; Luo, Tingting; et al. (Frontiers in Genetics, 2020)
Background Non-invasive prenatal testing (NIPT) is a commonly employed clinical method to screen for fetal aneuploidy, while the Y chromosome-based NIPT method is regarded as the gold standard for the estimation of fetal fraction (FF) of male fetuses. However, when the fetus has a derivative Y chromosome thereby containing a partial Y chromosome, the Y chromosome-based NIPT method cannot accurately calculate FF. Therefore, alternative methods to precisely calculate FF are required. Methods Two prenatal cases could not be detected effectively using the Y chromosome-based NIPT method because of low FF. According to the Y chromosome-based method, the FF of the fetuses were 1.730% ± 0.050% (average gestation week: 18+1) and 2.307% ± 0.191% (average gestation week: 20+0) for cases 1 and 2, respectively. Using various genetic diagnostic techniques, including the BoBsTM assay, karyotype analysis, improved nucleolus-organizing region (NOR)-banding analysis, Affymetrix CytoScan 750K Array, and FISH analysis, we determined the genetic defects of two fetuses with translocations of the SRY locus. Further, we reassessed the FF using FF-QuantSC and X chromosome-based methods. The distribution diagram of reads for chromosome Y was also analyzed. Results The FF of the fetuses determined by FF-QuantSC were 10.330% (gestation week: 18+4) in case 1 and 9.470% (gestation week: 21+4) in case 2, while the FF of the fetuses determined using the X chromosome-based method were 8.889% (gestation week: 18+4) in case 1 and 2.296% (gestation week: 21+4) in case 2. Both the distribution diagrams of reads for chromosome Y of the two cases showed the deletion in the long arm of the Y chromosome. Conclusion For repeatedly low FF samples detected using the Y chromosome-based NIPT method for a long gestational week, we believe that FF-QuantSC and distribution diagrams of reads could be used as a supplement to NIPT, especially for rare cases of sex reversal caused by SRY translocation.